2016
DOI: 10.1007/s00249-016-1162-x
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for homogeneous preparation of stable monomeric and oligomeric forms of activated Vip3A toxin from Bacillus thuringiensis

Abstract: Bacillus thuringiensis vegetative insecticidal proteins like Vip3A have been used for crop protection and to delay resistance to existing insecticidal Cry toxins. However, little is known about Vip3A's behavior or its mechanism of action, and a structural model is required. Herein, in an effort to facilitate future crystallization and functional studies, we have used the orthogonal biophysical techniques of light scattering and sedimentation to analyze the aggregation behavior and stability of trypsin-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…The SDS-PAGE analysis of the elution peak shows two bands of 66 kDa and 19 kDa, which indicates that these two molecules remain associated under native conditions, as was previously reported [30]. The elution of the processed protein from the gel filtration column as a high molecular mass protein (the exclusion limit of the column is 100 kDa) is in agreement with a recent study that shows that the trypsin-activated Vip3Aa protein aggregates in solution to form an oligomer or because the protein may adopt a non-globular shape [31]. Other examples are known of proteins where, after activation, the two main fragments remain together and co-elute chromatographically.…”
Section: Discussionsupporting
confidence: 90%
“…The SDS-PAGE analysis of the elution peak shows two bands of 66 kDa and 19 kDa, which indicates that these two molecules remain associated under native conditions, as was previously reported [30]. The elution of the processed protein from the gel filtration column as a high molecular mass protein (the exclusion limit of the column is 100 kDa) is in agreement with a recent study that shows that the trypsin-activated Vip3Aa protein aggregates in solution to form an oligomer or because the protein may adopt a non-globular shape [31]. Other examples are known of proteins where, after activation, the two main fragments remain together and co-elute chromatographically.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the finding that the trypsin cleavage products of Vip3Aa16 (82% identical to Vip3Ag4) remain associated [26] and may indicate that the proteolytically cleaved complex is the active form of the toxin. The sensitivity of S. exigua larvae to Vip35Aa in full-length or trypsin-processed forms shows no significant difference [24]. Since trypsin-like cleavage of the full-length form would be expected in vivo in the insect gut, these results show that trypsin cleavage does not reduce activity and the processed form may be the active agent.…”
Section: Resultsmentioning
confidence: 95%
“…There is a further shoulder to this peak (~70 min) that appears to represent monomeric Vip3Ag4. A recent study with Vip3Aa35 (82% identical to Vip3Ag4), activated with trypsin, indicated the presence of aggregated, monomeric and tetrameric forms of this protein; the proportions of these forms could be manipulated by changing buffer conditions [24]. Fractions corresponding to the putative tetrameric form of Vip3Ag4, chosen to exclude those that might include the monomeric form were combined and the protein was concentrated to 1 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Both the protoxin and the activated form of the Vip3 proteins are homo‐tetramers in solution . The 3D structure of the Vip3A tetrameric protein has been reported though at lower resolution . The improved structural information aids in the development of transgenic crops expressing genetically engineered chimeric Vip3A protein with higher insecticidal activity.…”
Section: Structure Of Vip3a Proteinsmentioning
confidence: 99%
“…Vip3A family proteins have been successfully used to control pest Lepidoptera. Several studies on the structure, function and mode of action of Vip3A have already been conducted but a clear understanding of its mechanism of action is lacking . The Vip3A family has a large number of proteins, and these proteins have different levels of insecticidal activity against closely related insect species.…”
Section: Future Research Needsmentioning
confidence: 99%